Nitric oxide modulates the release of corticotropin-releasing hormone from the rat hypothalamus in vitro. - Costa, A; Trainer, P; Besser, M; Grossman, A (1993)
There is now considerable evidence that nitric oxide (NO) is an important neuroregulatory agent, but there has been very little investigation of the possible role of NO in neuroendocrine mechanisms. We have previously shown that acute rat hypothalamic explants can be used to study the regulation of hypothalamic neuropeptide release, and we have now utilised this experimental approach to investigate the putative involvement of NO in the control of the principal corticotropin-releasing hormone, CRH. We studied the direct effects of the NO precursor L-arginine (L-ARG), as well as the NO donors molsidomine and sodium nitroprusside, on both the basal and stimulated release of CRH; the stimuli used were non-specific depolarisation with potassium chloride (KCl) and the specific cytokine, interleukin-1 beta (IL-1 beta; 100 U/ml). L-ARG was tested in each experimental condition with and without contemporaneous addition of its competitive antagonist NG-monomethyl-L-arginine (L-NMMA). IL-1 beta-induced CRH release was also investigated in the presence of D-arginine (D-ARG), which is not active as a precursor to NO, and ferrous hemoglobin (Hb), a substance which is a potent inactivator of NO. None of the NO precursors (L-ARG, molsidomine, sodium nitroprusside) or antagonists (L-NMMA or Hb) was able to affect basal CRH release. However, L-ARG 10 and 100 microM were found to significantly inhibit the release of CRH induced by 40 mM KCl; CRH fell to 45% of its stimulated level at the higher dose of L-ARG. This effect was attenuated in the presence of L-NMMA at a ten-fold higher dose.(ABSTRACT TRUNCATED AT 250 WORDS)